“Real men”, “Proper ladies” and mixing in-between : a qualitative study of social cohesion and discrimination in terms of race and gender within residences at Stellenbosch University - Robertson, Megan Aimee (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.